(untitled) (Journal of Hama University, 2026)
Introduction: Edentulous patients suffer that they have only the residual alveolar ridges to support complete denture, if no effort is made to preserve them, these patients will progressively experience more difficulty in attempting to obtain aesthetic and efficient service from complete dentures. Researchers emphasized the importance of preserving the residual Osseous Structures and described methods for accomplishing this goal. many dental medical studies indicating that the Occlusal Vertical Dimension is one of the most important factors influencing the bone resorption, and thus has a significant role to play in maintaining the Osseous structures under complete dentures. Purpose: This research aims to study the effect of reducing 3mm of Occlusal Vertical Dimension in patients with complete dentures on the Osseous Structures of mandibular bone. Materials and methods: The research sample consisted of ten edentulous patients, eight males and two females, aged between 46 and 70, complete dentures are designed to make One upper denture and two lower dentures for each patient in the research sample. The lower denture in the first stage were designed with a Suitable Occlusal Vertical Dimension, and after delivering them to the patients and following up for 3 months, the Occlusal Vertical Dimension was adjusted and reduced by 3 mm in the second stage, then it was delivered to the patients and they were also followed up for another 3 months. 3 panoramic radiographs were taken for each patient and the necessary measurements were made. Results: the arithmetic mean of the values of the amount of bone resorption occurring in the Suitable Occlusal Vertical Dimension stage was 0.67 mm, while the arithmetic mean of the values of the amount of bone resorption occurred in the Reduced Occlusal Vertical Dimension stage 0.32 mm, and at the 95% confidence level Statistically significant bilateral differences were found in the values of the amount of bone resorption (in mm) between the two stages studied. Conclusion: The bone resorption rate after the Suitable Occlusal Vertical Dimension stage is higher than that, after Reducing the Occlusal Vertical Dimension in the second stage, and therefore, Bone resorption decreased slightly, after reducing the Occlusal Vertical Dimension by 3 mm.